Effect of silicon–aluminum additives on ash fusion and ash mineral conversion of Xinjiang high-sodium coal. (1st October 2016) - Wei, Bo; Wang, Xuebin; Tan, Houzhang; Zhang, Limeng; Wang, Yibin; Wang, Zhao
Abstract: The high sodium content in Xinjiang coal ash induces severe fouling and slagging in pulverized coal furnaces. To solve these problems, many people have reported to use silicon–aluminum additives. In this paper, the effects of silicon–aluminum additives (SiO2, kaolin, and fly ash) on ash fusion characteristic, mineral transformation, and sodium emission were investigated. The results showed that the ash fusion temperatures (AFTs) manifested a pattern of decrease first and increase later along with an increasing in silicon–aluminum additive ratios. To achieve higher AFTs than that of raw coal ash, the blending proportion of silicon–aluminum additives is recommended as high as 9%. The causes for these results were explored. When the proportion of the additives was 3%, Ertixiite (Na2 Si2 O5 ), nepheline (NaAlSi3 O8 ), lazurite (Na7 Al6 Si6 O24 S3 ) and hauyne (Na6 Ca2 Al6 Si6 O24 (SO4 )2 ), were formed at 1150 °C. These species with low melting temperatures are flux minerals and lower ash fusion temperature, resulting in the lowest AFTs. This is the main cause of lower ash fusion point in the case of lower blending ratios. Moreover, almost all of the tested additives show the capability of capturing sodium, in which, the capturing capability of SiO2 is the best. For sodium capture capacity of the three additives under most tested conditions, the optimum temperature was around 1000 °C.